Polymorphisms in the IRF‐4 gene, asthma and recurrent bronchitis in children. Issue 10 (16th September 2013) - Pinto, L. A.; Michel, S.; Klopp, N.; Vogelberg, C.; von, A.; Bufe, A.; Heinzmann, A.; Laub, O.; Simma, B.; Frischer, T.; Genuneit, J.; Gorski, M.; et al.
Summary Background Interferon‐regulatory factors (IRFs) play a crucial role in immunity, not only influencing interferon expression but also T cell differentiation. IRF‐4 was only recently recognized as a further major player in T cell differentiation. Objective As IRF‐1 polymorphisms were shown to be associated with atopy and allergy, we comprehensively investigated effects of IRF‐4 variants on allergy, asthma and related phenotypes in German children. Methods Fifteen tagging single nucleotide polymorphisms (SNPs) in the IRF‐4 gene were genotyped by MALDI‐TOF MS in the cross‐sectional ISAAC phase II study population from Munich and Dresden (age 9–11; N = 3099). Replication was performed in our previously established genome‐wide association study (GWAS) data set (N = 1303) consisting of asthma cases from the Multicenter Asthma Genetic in Childhood (MAGIC) study and reference children from the ISAAC II study. Results SNPs were not significantly associated with asthma but with bronchial hyperresponsiveness, atopy and, most interestingly, with recurrent bronchitis in the first data set. The IRF‐4 variant rs9378805 was associated with recurrent bronchitis in the ISAAC population and replicated in the GWAS data set where further SNPs showed associations with recurrent bronchitis and asthma. Conclusions We found genetic associations in IRF‐4 to be associated with recurrent bronchitis in our two study populations. Associated polymorphisms are localized in a putative regulatory element in the 3′UTR region of IRF‐4. These findings suggest a putative role of IRF‐4 in the development of bronchitis.